Criminalization toward LGBT Community and its Implementation through the Aceh Qanun in Indonesia - M. Hamdan1 , Eva Syahfitri Nasution1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This paper discussed some Criminal Laws on LGBT community regulated in the Criminal Code and in special legal provisions outside the Criminal Code. It also discussed criminalization toward LGBT people through the Aceh Perda, regulated in the Aceh Qanun and its implementation through the Banda Aceh Sharia Court. In the criminal law stipulated in the Indonesian Criminal Code today and in the legal provisions outside the Penal Code, some of the illegal acts committed by LGBT people are liable to imprisonment. The criminal law stipulated in the Aceh Qanun cleanly regulates the acts of lesbian and gay people as the ones which are strictly prohibited and liable to being punished. Therefore, based on this Aceh Qanun, their acts are considered as criminal acts. Aceh Qanun (which is considered as the Aceh Perda or Government Regulation), has criminalized the acts of LGBT people. In Aceh, committing sexual intercourse of gays and lesbians has been formulated in Article 63 and Article 64 of the Aceh Qanun No. 6/2014. The violation against these Articles has been implemented on the perpetrators who are punished with ‘uqubat’ or whipped 85 times before public as it is found in the Banda Aceh Sharia Court’s Verdict No. 19/JN/2017/Ms.Bna on May 17, 2017